2018
DOI: 10.1155/2018/6824643
|View full text |Cite
|
Sign up to set email alerts
|

Primary Leiomyosarcoma of the Colon: A Report of Two Cases, Review of the Literature, and Association with Immunosuppression for IBD and Rheumatoid Arthritis

Abstract: Primary leiomyosarcomas (LMS) of the colon are rare and aggressive neoplasms and have been infrequently reported in the literature. These tumors are more aggressive and have poorer prognoses than adenocarcinoma of the colon and are often mistaken as such on initial evaluation. While the former has a clear association with inflammatory bowel disease (IBD), this correlation is not known to exist with LMS and IBD. Nor is there a known link between LMS and the immunosuppression for IBD, despite the known associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Yamamoto et al, concluded that the only negative predictive factor for survival is tumor size of more than 5 cm [16] . However, based on previous case studies local and distal recurrence occurred even with favorable tumor features [14] . Compared with adults, infantile LMS has a better prognosis even with poor histologic features [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamoto et al, concluded that the only negative predictive factor for survival is tumor size of more than 5 cm [16] . However, based on previous case studies local and distal recurrence occurred even with favorable tumor features [14] . Compared with adults, infantile LMS has a better prognosis even with poor histologic features [17] .…”
Section: Discussionmentioning
confidence: 99%
“…True LMS of the colon is such a rare disorder that there isn't enough description of its nature. The classical colon LMS presents with a vast majority of non-specific symptoms including mild abdominal pain, fresh/obscure rectal bleeding, intra-abdominal hemorrhage, weight loss, changes in bowel habits, bowel obstruction, and tenesmus [14] . Diagnosis is based on colonoscopy and histologic evaluation and IHC profiling.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al, concluded that the only negative predictive factor for survival is tumor size of more than 5 centimeters [15]. However, based on previous case studies local and distal recurrence occurred even with favorable tumor features [13].…”
Section: Discussionmentioning
confidence: 99%
“…The classical colon LMS presents with a vast majority of non-speci c symptoms including mild abdominal pain, fresh/obscure rectal bleeding, intraabdominal hemorrhage, weight loss, changes in bowel habits, bowel obstruction, and tenesmus. [13] Diagnosis is based on colonoscopy and histologic evaluation and IHC pro ling.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 These colonic leiomyosarcomas have been reported primarily in Japan. 1 , 2 Only a few articles have come out about PLC in the United States. 1 , 4 PLC are aggressive tumors with a 5-year survival of 45.6%.…”
Section: Introductionmentioning
confidence: 99%